The Rise of Fascism in Italy: Versions and Critiques - N. E. Zonova (Концепт: философия, религия, культура, 2022)
A century ago, on October 28th Benito Mussolini and twenty thousand members of his National Fascist Party marched on Rome. Prime minister Luigi Facta assured the king that Italian armed forces could resist the few on the march and suggested declaring a state of emergency. King Victor Emmanuel III and his elite for two years had been watching with apprehension the rise of the communist left and sought a strong hand to curb disorders. Mussolini was counting on that and was quick to react. He receded from his socialist views and eagerly propounded his antisocialist ideology and vowed to put an end to antigovernmental strikes. Once Mussolini became prime minister, it marked the beginning of the formation of a totalitarian regime in Italy. At that time Italy was devastated by the war that ended with a Mutilated victory and was on the brink of bankruptcy. Mussolini exploited people’s sentiments of betrayal and dissatisfaction only to initiate rapprochement with Nazi Germany and draw the country into yet another war. In the recently published book on the rise of Mussolini, the authors clearly allude to the involvement of British money in the creation of the fascist party in Italy. Though British and French conservatives did transfer certain money to Mussolini, the proposed thesis is a clear exaggeration. It was the internal situation in Italy that gave rise to fascism. And today’s policy of the ruling coalition led by Giorgi Meloni does not coincide in any way with the signs of fascism listed by Umberto Eco.